LICHEN IN THE AREA OF IE SEU UM OF MESJID RAYA DISTRICT ACEH BESAR REGENCY - Lisa Rauzatul Maretia; Samingan Samingan; Hasanuddin Hasanuddin; Wardiah Wardiah; Cut Nurmaliah (Biotik, 2021)
Crust moss (lichen) is a symbiotic organism between fungi and algae which play important roles in environment and can grow in extreme conditions. Therefore, those are important issues to be concerned. The study was aimed to identify the lichen species and their substrates in the Ie Seu um area of Mesjid Raya District, Aceh Besar Regency. This research used exploratory survey methods. Observations were done at radii of 10, 20 and 30 meters from the hot spring. The parameters of the study were lichen species, types of thallus and substrate. Besides, the parameters consisting of air temperature and humidity, and light intensity were also measured. Data was analyzed descriptively and was revealed in tables and figures. The results  showed that there were 16 lichen species consisting of 7 species (at radius of 10 meters), 6 species (at radius of 20 meters), and 9 species (at radius of 30 meters). From the total species, there were 12 crustose-thallus species and 4 foliose-thallus species. The substrate types serve as the habitat of lichen were trees, stones and dead wood.